2009
DOI: 10.1142/s021909150900168x
|View full text |Cite
|
Sign up to set email alerts
|

The Extended Opening Session of the Futures Market and Stock Price Behavior: Evidence from the Taiwan Stock Exchange

Abstract: This paper examines how the introduction of the extended opening session of the futures market affects stock price behavior around the market opening. On January 1, 2001, the Taiwan Futures Exchange (TAIFEX) extended the trading hours by opening earlier 15 minutes than the Taiwan Stock Exchange (TWSE). This change presents an opportunity to analyze how the extended opening session * Corresponding author. 403 Rev. Pac. Basin Finan. Mark. Pol. 2009.12:403-416. Downloaded from www.worldscientific.com by UNIVERSIT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 16 publications
1
3
0
1
Order By: Relevance
“…However, they did observe an increase in the bid-ask spread, which is considered to be a transaction cost. A study of the Japanese futures market conducted by Miwa (2019), found that the extension of trading hours negatively affected price formation, which supports the earlier findings of Lee, Chien, Chen, and Huang (2009) and Miwa and Ueda (2017).…”
Section: Literature Summarysupporting
confidence: 79%
See 1 more Smart Citation
“…However, they did observe an increase in the bid-ask spread, which is considered to be a transaction cost. A study of the Japanese futures market conducted by Miwa (2019), found that the extension of trading hours negatively affected price formation, which supports the earlier findings of Lee, Chien, Chen, and Huang (2009) and Miwa and Ueda (2017).…”
Section: Literature Summarysupporting
confidence: 79%
“…The simultaneous replacement of the midday SPCA and LB with MPCT on Borsa Istanbul Equity Market on 4 October 2019 also led to the extension of trading hours. Barclay and Hendershott (2003), Fan and Lai (2006), Houston and Ryngaert (1992), Lee et al (2009), Miwa and Ueda (2017) and Miwa (2019) investigated the effect of trading-hour extension on volatility in equity and futures markets. However, these studies analysed trading-hour extensions caused by introducing call auction at opening or closing of continuous trading and found that the extension of trading hours had no positive effect on intraday volatility.…”
Section: Literature Summarymentioning
confidence: 99%
“…The TAIFEX extended trading hours by opening earlier 15 min than the TWSE. Lee et al (2009b) show that stock returns are less volatile and return autocorrelations are less positive around the stock market opening, and overreaction of opening prices in the stock market is mitigated in the post-extension period. 5 There are other popular representations of basis including the root of mean square ð ffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffi ðF t À S t Þ 2 p Þ, consecutive maturity first difference ðF 2t À F 1t Þ, ðlog F t À log S t Þ, and return ðR F The selection of this test period, however, is not without consequence.…”
Section: Data and Marketsmentioning
confidence: 95%
“…Cheng et al (2004) explored the trading day extension made in the Hang Seng Index Futures and concluded that the extended trading hours conveyed useful information about spot prices. Lee et al (2009) tested the impact of an early extension (in January 2001) in the Taiwan Futures Exchange (TAIFEX) on stock prices. The reform involved a 15-min extension for the futures market, while the opening time of the Taiwan Stock Exchange remained the same.…”
Section: Literature Reviewmentioning
confidence: 99%